Efisiensi Teknis, Alokatif, Dan Ekonomi Usahatani Tembakau Di Kabupaten Lumajang (Pendekatan Stochastic Frontier) - Susanti, Irma; Sujarwo, Sujarwo; Suhartini, Suhartini (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Tobacco is one of the plantation commodities with strategic value in Lumajang Regency. However, the sustainability of tobacco farming in Lumajang Regency is faced with various challenges, including a decrease in productivity. To achieve high productivity, tobacco farming must be carried out efficiently so that extra skills are needed from each individual farmer. This research aims to analyze the factors that influence production and the level of technical, allocative and economic efficiency of tobacco farming in Lumajang Regency. Data collection was carried out using a survey method on 68 farmer respondents. The stochastic frontier production function is used in this research for data analysis. The research results show that the factors that influence tobacco production in Lumajang Regency are land area, P fertilizer, K fertilizer, and liquid pesticides. The average achievement of technical, allocative and economic efficiency of tobacco farming in Lumajang Regency is 0.71; 0.57; and 0.40. To achieve an economically efficient level, farmers need to improve their technical and allocative efficiency achievements.